Peran Guru Dalam Menggunakan Model Contextual Teaching and Learning (CTL) di Sekolah Dasar - Dahlia Mei Frida Silitonga; Elpri Darta Putra (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
Lack of teachers in organizing the material with the real life of students so that the learning process seems meaningless. The teacher is one of the determining factors for the success of any educational effort and the teacher has a very important role in the learning process. To organize subject matter with students' daily lives, teachers need to improve how to teach well and teachers are able to choose the right learning methods for teaching. The CTL learning model is a learning model in which a conception that helps learning activities connect the content of teaching materials with students' real world situations. This study aims to find out how the teacher's role in implementing the contextual teaching and learning (CTL) model for elementary school students. This type of research is qualitative research. The research was conducted in class V of Pekanbaru Adventist Elementary School, with 3 teachers and 3 students as the subject. Methods of data collection using interviews, observation and document review. Data analysis used descriptive qualitative analysis. The results of the study indicate the teacher's role in using contextual teaching and learning (CTL), it can be seen that the teacher does planning such as preparing lesson plans, then the teacher carries out the learning process using the CTL model. Furthermore, the teacher also the results of the learning that has been done.